(untitled) (Rheumatology Reports, 2012)
Behçet’s disease is a systemic vasculitis of unknown aetiology that may involve veins and arteries of all sizes. It occurs most commonly in the second or third decades of life and it is characterised by recurrent oral and genital ulceration and chronic relapsing uveitis. We present here a case of Behçet’s disease complicated by an inflammatory aortitis successfully treated with infliximab and endovascular stenting.